2014
DOI: 10.1080/10942912.2013.779700
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Roselle(Hibiscus Sabdariffa L.) Seed Protein Hydrolysate and its Derived Peptide Fractions

Abstract: In this study, peptide fractions with strong antioxidant activity were obtained from Roselle seed protein hydrolysates. Pepsin followed by pancreatin were used to digest Roselle protein at different time in order to produce hydrolysate with antioxidant activity suitable for conversion to high-value products. The hydrolysates obtained after different hydrolysis times were analyzed for antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl radical scavenging method. The 3 h hydrolysate showed the highest antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
1
16
1
Order By: Relevance
“…The Degree of hydrolysis (DH) is generally used as a parameter for monitoring proteolysis and is the most widely used indicator for comparison among different protein hydrolysates. The results showed that the DH of RSPH1.5 was 15.82% which was lower than that observed at 3 hours hydrolysis time (21.56 %) (Tounkara et al, 2013b).…”
Section: Results and Discussion Enzymatic Hydrolysismentioning
confidence: 54%
“…The Degree of hydrolysis (DH) is generally used as a parameter for monitoring proteolysis and is the most widely used indicator for comparison among different protein hydrolysates. The results showed that the DH of RSPH1.5 was 15.82% which was lower than that observed at 3 hours hydrolysis time (21.56 %) (Tounkara et al, 2013b).…”
Section: Results and Discussion Enzymatic Hydrolysismentioning
confidence: 54%
“…The increase of the ABTS radical scavenging activity of the samples after the in vitro digestion may be assigned to the release of peptides with antioxidant activity and/or the increase of the antioxidant activity of compounds (polyphenols) that were attached to the proteins, [31][32][33] while we cannot associate the absorption of oxygen radicals to polyphenols or proteins. Further studies are needed to identify the compound or compounds responsible for both activities.…”
Section: Antioxidant Capacitymentioning
confidence: 86%
“…These activities were similar to those of digested A. mantegazzianus proteins and to the activities of other plant proteins subjected to hydrolytic treatments. [19,30,31] The antioxidant capacity of the samples was also analyzed using the ORAC assay. Results obtained (Table 2) indicate that seeds and sprouts isolates presented a similar ability to absorb oxygen radicals while the SS showed greater activity.…”
Section: Antioxidant Capacitymentioning
confidence: 99%
“…CPC, the major phycobiliprotein in S. platensis, contained high level of glutamic acid (GLU), aspartic acid (ASP), alanine (ALA), leucine (LEU), arginine (ARG), isoleucine (ILE), serine (SER), glycine (GLY), and threonine (THR), [40] most of which have been reported to be related to higher antioxidant activity levels. [41] The antioxidant activities of the food-grade phycocyanin solution were evaluated by the ABTS and DPPH methods, which are often used in the determination of the antioxidant abilities of natural compounds. [32,42] The ABTS radical-scavenging activity of phycocyanin solution at different concentrations is shown in Fig.…”
Section: Antioxidant Activity Of Phycocyaninmentioning
confidence: 99%